Study on microstructures and mechanical properties of super narrow gap joints of thick and high strength aluminum alloy plates welded by fiber laser. Issue 1 (January 2016) - Zhang, Z.; Dong, S.; Wang, Y.; Xu, B.; Fang, J.; He, P.
Abstract The welding of thick high strength aluminum alloy plate was exceedingly difficult. Traditional arc welding was prone to softening the welded joints and involves multilayer; meanwhile, multi-pass welding may cause great residual welding stress, and deformation resulted in dampening the wide expansion of the welding structure of thick high strength aluminum alloy plates. Therefore, it was urgent to develop advanced materials and welding technologies to enhance the comprehensive mechanical properties of welded joints. Fiber laser boasted the advantages such as perfect monochromaticity and high quality light beam. In order to decrease the thermal loss of the welding heat source on the matrix, small power fiber laser and super narrow gap groove were applied for the effective welding of the 20-mm thick 7A52 aluminum alloy. The welding adopted multilayer and single pass welding with the groove width no wider than 4 mm. The weld was composed of four layers and the size was no wider than 4.5 mm, which was basically consistent with the widths of the whole. The parent metal was welded with 5183 alloy and 5E06 alloy. Fiber optical microscope, scanning electron microscope (SEM), transmission electron microscope (TEM), and tensile testing machine were employed to investigate the influence of Er-Zr microalloying aluminum alloy welding wires upon the microstructure and mechanical properties of the welded joints.